TCA cycle impairment leads to PIN2 internalization and degradation via reduced MAB4 level and ARA6 components in Arabidopsis roots - Song, Xiaomin; Ohbayashi, Iwai; Sun, Song; Wang, Qiuli; Yang, Yi; Lu, Mengyuan; Liu, Yuanyuan; Sawa, Shinichiro; Furutani, Masahiko (Frontiers in Plant Science, 2024)
The mitochondrial pyruvate dehydrogenase complex (PDC) plays a crucial role in linking the glycolysis pathway and the tricarboxylic acid (TCA) cycle. Previously, we reported that a mutation of MAB1, encoding an E1β subunit of PDC, affects the abundance of auxin efflux carriers PIN-FORMED proteins (PINs) via reduced recycling and enhanced degradation in vacuoles. Here, we further analyzed the effects of TCA cycle inhibition on vesicle trafficking using both the mab1-1 mutant and 3-BP, a TCA cycle inhibitor. Pharmacological and genetic impairment of the TCA cycle induced the aggregated components of ARA6, which is a plant-unique RAB5 GTPase that mediates endosomal trafficking to the plasma membrane. In addition, MAB4, which is an NPH3-like protein that inhibits PIN internalization from the plasma membrane, was severely reduced in 3-BP-treated roots and mab1-1. Furthermore, TCA cycle impairment led to the accumulation of reactive oxygen species in root tips, and treatment with H2O2 reduced MAB4 levels while increasing the internalization of PIN2 from the plasma membrane, and aggregated ARA6-positive compartments. These results suggest that TCA cycle impairment targets PIN proteins for degradation in the vacuole by disrupting both the MAB4-mediated block of internalization and the ARA6-mediated endocytic pathway.